Image Encryption Using RK-RSA Algorithm in Aadhaar Card - et.al, R. Felista Sugirtha Lizy (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Cryptography is used for secretly sending information. The information or given data is protected by cryptographic technique. The technique is used in Text and images. The technique is supported by a lot of algorithms. RSA is a better encryption technique for smart cards. In this paper, an image in the Aadhaar card is encrypted using the RK-RSA algorithm for better protection and confidentiality. The proposed RK-RSA algorithm is very secure for smart cards and Aadhaar cards. The better performance of the RK-RSA is evaluated based on the Avalanche Effect, Speed, Throughput, and Power Consumption. The improved performance of the RK-RSA algorithm’s experimental results is reported. The mathematical justification supporting the RK-RSA algorithm is also detailed.